Grammatical Gender Features in English and Arabic (Journal of the College of Basic Education, 2023)
Gender in language is like sex in the outside world . Sex is considered as the most important basis for gender distinction . Sex stands for either male or female creatures.The main purpose behind this paper is to provide a comparative study between English and Arabic gender . It deals with gender as a grammatical category . The paper is divided into three sections: Section one gives an account of the term gender ; Section two deals with gender in Arabic while section three displays gender in English then the conclusion of the study is displayed . It reflects the main points of contrast between the two languages under study as far as gender is concerned .The distinction of gender into feminine and masculine is an important feature in Arabic , Unlike English where the majority of words do not make this distinction clear .In addition, Languages differ in the number of gender they recognize . English has three genders masculine , feminine and neuter which stand respectively for male , female and neither sex . On the other hand , Arabic has two gender categories : masculine and feminine. Both languages under study use the natural gender in classifying the nouns into masculine and feminine. i.e. every noun that belongs to the class of masculine nouns refers to male animate and vise versa.In Arabic ,masculine nouns are considered as the basis from which feminine nouns can be derived through the addition of certain markers . These markers can be added to both nouns and adjectives , whereas , a few nouns in English are marked for gender . In Arabic , there are certain irregularities inconsidering and forming the feminine nouns whereas in English some pronouns are gender sensitive.On the syntactic level , In Arabic , there should be an agreement between the noun that is marked for gender and the other elements of the sentence while in English such agreement can be manifested between the nouns and their pronouns in the singular case only.